2017
DOI: 10.1177/0093854817714810
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pathways to Juvenile Recidivism: Examining Parental Drug and Mental Health Problems, and Markers of Neuropsychological Deficits Among Serious Juvenile Offenders

Abstract: The current study examines multiple pathways to antisocial behavior involving neurobiologically based measures and indicators of executive functioning in the interest of informing treatment and intervention services for the deepest end juvenile justice placements. Specifically, using a statewide, multiyear sample of over 11,000 male juvenile offenders completing residential commitment placements, we employ structural equation modeling (SEM) to examine whether parental drug, alcohol, and mental health problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…In an early study, Teplin et al (2002) observed that the prevalence rates of ADHD were similar between Black, White, and Hispanic JIY. Baglivio et al (2017), however, reported that Black and Hispanic JIY were less likely to have a history of ADHD. Black children and children of other racial makeups diagnosed with ADHD were more likely than White children (Soltis et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…In an early study, Teplin et al (2002) observed that the prevalence rates of ADHD were similar between Black, White, and Hispanic JIY. Baglivio et al (2017), however, reported that Black and Hispanic JIY were less likely to have a history of ADHD. Black children and children of other racial makeups diagnosed with ADHD were more likely than White children (Soltis et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Prior studies examining substance use disorders using the NSDUH measures have shown acceptable reliability and validity (Fearn et al., 2016; Grucza et al., 2007; Jordan et al., 2008). Mental health and personality characteristics Depression, risk propensity and mental health treatment history were used in our study based on their association with justice system involvement (Baglivio et al., 2017; Vaughn et al., 2012, 2015). Depression and prior treatment were each rated dichotomously as yes/no.…”
Section: Methodsmentioning
confidence: 99%
“…Mental health and personality characteristics Depression, risk propensity and mental health treatment history were used in our study based on their association with justice system involvement (Baglivio et al., 2017; Vaughn et al., 2012, 2015). Depression and prior treatment were each rated dichotomously as yes/no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation